1987
DOI: 10.1002/j.1460-2075.1987.tb02409.x
|View full text |Cite
|
Sign up to set email alerts
|

The human mid-size neurofilament subunit: a repeated protein sequence and the relationship of its gene to the intermediate filament gene family.

Abstract: We report the isolation and sequence of cDNA and genomic clones for one of the two large subunits of human neurofilament, NF-M. Analysis of the sequence has allowed us to investigate the structure of the carboxy-terminal tail of this protein, and to compare it to that of the small neurofilament as well as to other intermediate filaments. The carboxyterminal region of the protein contains a 13 amino acid prolineand serine-rich sequence repeated six times in succession. Within each repeat unit are two smaller re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
174
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(187 citation statements)
references
References 64 publications
10
174
0
Order By: Relevance
“…The mouse and human NF-H messages are fairly similar with 43 and 40 repeat sequences, respectively, whereas the rat NF-H has 51 repeats ( fig.3). A similar interspecies difference has also previously been ...... noted in the corresponding region of NF-M [4,[9][10][11]. In the rat NF-H cDNA sequence, 41 of the triplet Lys-Ser-Pro repeats occur in a regular pattern of six amino acids ( fig.3).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The mouse and human NF-H messages are fairly similar with 43 and 40 repeat sequences, respectively, whereas the rat NF-H has 51 repeats ( fig.3). A similar interspecies difference has also previously been ...... noted in the corresponding region of NF-M [4,[9][10][11]. In the rat NF-H cDNA sequence, 41 of the triplet Lys-Ser-Pro repeats occur in a regular pattern of six amino acids ( fig.3).…”
Section: Resultssupporting
confidence: 74%
“…A small number of triplet repeats are also present in NF-M [9][10][11]18], but are absent from NF-L [6][7][8]. Previous studies have shown that the number of alkaline phosphatase-sensitive phosphate groups on NF-H and NF-M are approximately proportional to the number of triplet repeats, these phosphate groups being absent from NF-L [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all peptides must have contained phosphoserine residues after the first dimension, a filled circle above a serine is only used for those peptides where the particular phosphorylated serine is clearly identified (see text). Sequences Ml-M3 are tentatively arranged along the corresponding regions of the human and rat proteins [14,15]. Numbers on the right reflect position number of the last residue from these regions.…”
Section: Resultsmentioning
confidence: 99%
“…The less abundant species (5%) started 4 residues prior to the methionine. From the isolation of a tryptic peptide corresponding to residues 861-872 in the human sequence [14] we assume that the M tail isolated after chymotryptic cleavage lacks the carboxy-terminal 43 residues of porcine NF-M.…”
Section: Resultsmentioning
confidence: 99%